Osmanlı Hukukunda Bürokratik Geleneğin Tesisi: Bursa Kadılığı ve Kadı Sicillerinin Oluşumu - HABIB, HABIBULLAH (My University, 2024)
The emergence of records and registers in the Ottoman judicial and administrative bureaucracy remains a relatively unexplored question within Ottoman history. This study aims to examine this question with reference to the judicial registers of the Bursa court, which was the highest legal authority until the conquest of Edirne and the establishment of the office of kazasker (military judge). Bursa is of great importance as it was the city where the Ottoman judicial organization and the related bureaucratic structure were shaped, and it contains the earliest dated registers among the surviving judicial records and documents. Bursás judicial registers, especially those from the 15th century are the only surviving collection of registers in a book form in the Islamic world, and they constitute an indispensable source for Islamic and Ottoman legal studies. This article discusses the establishment of the Bursa court, its history, and its role in the establishment of the Ottoman bureaucratic tradition, along with the first judge of Bursa, the formation and importance of the judicial registers, and the earliest surviving registers of Bursa based on archival records.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (çeşitli); Social Sciences & Humanities; Arts and Humanities (miscellaneous); Bursa Court; Court Registers; Ottoman Bureaucracy; Ottoman Law